Dynamic Numerical Simulation of Hybrid Rocket Motor with HTPB-Based Fuel with 58% Aluminum Additives - Hui Tian; Xiangyu Meng; Hao Zhu; Chengen Li; Lingfei He; Guobiao Cai (Aerospace, 2022)
The addition of aluminum (Al) to the fuel is an effective way to increase the regression rate of hybrid rocket motors (HRMs). Due to its high regression rate, the impact of the regression of combustion surface on the performance of HRMs cannot be ignored. Therefore, it is significant to establish a dynamic numerical simulation model to predict the performance of HRMs. In this study, the dynamic simulation model was established based on dynamic mesh technology and was verified by a firing test. The results show that the simulation results agree well with the experimental results, and the errors of the average thrust and combustion chamber pressure are 3.4% and 1.4%, respectively. The dynamic simulation shows that with the regression of the combustion surface, the vortex of the pre-combustion chamber is divided into two vortices. The vortex near the front of the grain will increase the regression rate downstream. The results show that the addition of Al can obviously improve the regression rate of HRMs. The fuel containing 58% Al can improve the regression rate by 88.8% compared with the fuel with pure hydroxyl-terminated polybutadiene (HTPB). Moreover, due to the higher combustion temperature and the scouring of metal particles, the ablation rate of the nozzle with carbon ceramic materials reaches 0.16 mm/s. This investigation provides a valuable reference for HRMs design and simulation.